Comparison Of Dynamic Hip Screw (Dhs) And Proximal Femoral Nail (Pfn) Fixation For Unstable Intertrochanteric Femoral Fractures On Basis Of Collapse - Nasir Nawaz , Hamza Fareed , Sajida Shah , Inamullah Shah , Nasir Nawaz , Hamza Fareed , Sajida Shah , Inamullah Shah (Journal of Rawalpindi Medical College, 2019)
Introduction:Proximal femoral nail (PFN) is an intramedullary device for fixation of intertrochanteric femoral fracture and has shown promise in unstable intertrochanteric fractures, which have been treated with dynamic hip screw (DHS) till recently.Introduction:Proximal femoral nail (PFN) is an intramedullary device for fixation of intertrochanteric femoral fracture and has shown promise in unstable intertrochanteric fractures, which have been treated with dynamic hip screw (DHS) till recently.Objectives: To compare the frequency of collapse in the early postoperative period between fixation with DHS versus PFN in unstable intertrochanteric femoral fractures. Patients and methods: This randomized controlled trial was conducted at CMH Rawalpindi in 2017. A total of 310 male and female adult patients between 18 to 75 years in age, with unstable intertrochanteric fractures were included. Patients having pathological fractures, renal disease and open fracture were excluded. The patients were assigned randomly to one of the two groups. Group A was treated with DHS and Group B was treated with PFN. The collapse was measured initially on standard x-rays taken on the zero postoperative day. Patients were allowed to bear partial weight at 4 weeks and second measurement for collapse was done after 6 weeks postoperatively.Results: The mean age of patients in group A was 51.27 ± 11.54 years and in group B was 53.75 ± 12.28 years. Collapse was seen in 26 (16.77%) patients in group A (DHS) and 07 (4.52%) patients in group B (PFN) with p-value of 0.0001. Age has a bearing on the rate of collapse while BMI does not. Conclusion: The frequency of collapse in early postoperative period is less after treatment with proximal femoral nail as compared to dynamic hip screw in unstable intertrochanteric fractures.Keywords: Intertrochanteric femoral fractures; Unstable intertrochanteric fracture; proximal femoral nail; dynamic hip screw; sliding hip screw; collapse.